A Novel Direct Manipulation Technique for Motion-editing using a Timeline-based Interface - Natapon Pantuwong (My University, 2019)
Recently, motion data is becoming increasingly available for creating computer animation. Motion capture is one of the systems that can generate such motion data. However, it is not suitable to capture a lot of motion due to the cost of motion capture technique, and the diculty of its postprocessing. This paper presents a timeline-based motion-editing system that enables users to perform motion-editing tasks easily and quickly. A motion sequence is summarized and displayed in the 3D environment as a set of editable icons. Users can edit the motion data by performing a sequence of operations on a single key frame or over an interval. The recorded sequence is then propagated automatically to a set of target key frames or intervals, which can be either user dened or system dened. In addition, we provide a simple interaction method for manipulating the duration of specic intervals in the motion data. Methods for combining and synchronizing two dierent motions are also provided in this system. In contrast with the previous work that allows only temporal editing, the proposed system provides editing functions for both geometry and temporal editing. We describe a user study that demonstrated the eciency of the proposed system.
Keywords: Motion Capture; Synchronizing; Time line; Key frame; Sequence (biology); Structure from Motion; Interface (matter); Video editing; Human Motion and Animation